Comparison of the costs of nonoperative care to minimally invasive surgery for sacroiliac joint disruption and degenerative sacroiliitis in a United States Medicare population: potential economic implications of a new minimally-invasive technology - Ackerman SJ; Polly Jr DW; Knight T; Schneider K; Holt T; Cummings J (Dove Medical Press, 2013)
Stacey J Ackerman1, David W Polly Jr2, Tyler Knight3, Karen Schneider4, Tim Holt5, John Cummings61Covance Market Access Services Inc, San Diego, CA, USA; 2University of Minnesota, Orthopaedic Surgery, Minneapolis, MN, USA; 3Covance Market Access Services Inc, Gaithersburg, MD, USA; 4Covance Market Access Services Inc, Sydney, NSW, Australia; 5Montgomery Spine Center, Orthopaedic Surgery, Montgomery, AL, USA; 6Community Health Network, Neurosurgery, Indianapolis, IN, USAIntroduction: The economic burden associated with the treatment of low back pain (LBP) in the United States is significant. LBP caused by sacroiliac (SI) joint disruption/degenerative sacroiliitis is most commonly treated with nonoperative care and/or open SI joint surgery. New and effective minimally invasive surgery (MIS) options may offer potential cost savings to Medicare.Methods: An economic model was developed to compare the costs of MIS treatment to nonoperative care for the treatment of SI joint disruption in the hospital inpatient setting in the US Medicare population. Lifetime cost savings (2012 US dollars) were estimated from the published literature and claims data. Costs included treatment, follow-up, diagnostic testing, and retail pharmacy pain medication. Costs of SI joint disruption patients managed with nonoperative care were estimated from the 2005–2010 Medicare 5% Standard Analytic Files using primary International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) diagnosis codes 720.2, 724.6, 739.4, 846.9, or 847.3. MIS fusion hospitalization cost was based on Diagnosis Related Group (DRG) payments of $46,700 (with major complications - DRG 459) and $27,800 (without major complications - DRG 460), weighted assuming 3.8% of patients have complications. MIS fusion professional fee was determined from the 2012 Medicare payment for Current Procedural Terminology code 27280, with an 82% fusion success rate and 1.8% revision rate. Outcomes were discounted by 3.0% per annum.Results: The extrapolated lifetime cost of treating Medicare patients with MIS fusion was $48,185/patient compared to $51,543/patient for nonoperative care, resulting in a $660 million savings to Medicare (196,452 beneficiaries at $3,358 in savings/patient). Including those with ICD-9-CM code 721.3 (lumbosacral spondylosis) increased lifetime cost estimates (up to 478,764 beneficiaries at $8,692 in savings/patient).Conclusion: Treating Medicare beneficiaries with MIS fusion in the hospital inpatient setting could save Medicare $660 million over patients' lifetimes.Keywords: sacroiliac joint disruption, degenerative sacroiliitis, minimally invasive surgery, epidural injection, iFuse, cost